Inter-religious dialogue: the perspective of Malaysian contemporary Muslim thinkers - Aemy Elyani Mat Zain,; Jaffary Awang,; Idris Zakaria, (Universiti Kebangsaan Malaysia, 2014)
Malaysia is a country that is rich for the diversity of its people. This diversity can be seen from the aspect of faith, ethnicity, language, culture, and so on. In facing a society that is pluralistic in nature, several initiatives have been taken by the government and non-government bodies in ensuring understanding and unity among Malaysians. Among the initiatives taken are interreligious dialogues. In this regard, many among Malaysian thinkers have proposed some approaches and concepts of inter-faith dialogue that should and may be implemented in the context of Malaysia. For that purpose, this paper examined the forms of inter-religious dialogues in Malaysia from the perspective of Malaysian contemporary Muslim thinkers. The methodology utilized in this study is textual analysis, particularly the writings of these thinkers on this issue. This article concludes that there are several forms of inter-religious dialogues that are easily implemented, as well as the difficult ones in the context of Malaysia due to certain obstacles.